Tradition, transmission, and transformation from Second Temple literature through Judaism and Christianity in late antiquity : proceedings of the Thirteenth International Symposium of the Orion Center for the Study of the Dead Sea Scrolls and Associated Literature, jointly sponsored by the Hebrew University Center for the Study of Christianity, 22-24 February, 2011 - Kister, Menahem.; Newman, Hillel.; Segal, Michael, 1972-; Clements, Ruth. (Studies on the Texts of the Desert of Judah, 2015)
Many types of tradition and interpretation found in later Jewish and Christian writings trace their origins to the Second Temple period, but their transmission and transformation followed different paths within the two religious communities. For example, while Christians often translated and transmitted discrete Second Temple texts, rabbinic Judaism generally preserved earlier traditions integrated into new literary frameworks. In both cases, ancient traditions were often transformed to serve new purposes but continued to bear witness to their ancient roots. Later compositions may even provide the key to clarifying obscurities in earlier texts. The contributions in this volume explore the dynamics by which earlier texts and traditions were transmitted and transformed in these later bodies of literature and their attendant cultural contexts.